1989
DOI: 10.1210/jcem-68-6-1060
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Antagonism of Corticotropin-Releasing Hormone Stimulation of Prolactin Secretion in Rhesus Monkeys*

Abstract: The effect of opiate receptor blockade on human CRH-induced PRL secretion was examined in ovariectomized and normal female rhesus monkeys. A bolus iv dose of 100 micrograms CRH acutely stimulated PRL secretion in both normal and ovariectomized animals. The magnitude of the PRL response was greater in ovariectomized monkeys (212% increase; n = 5) than in normal monkeys (56% increase; n = 5). Naloxone pretreatment inhibited CRH-induced PRL release in a dose-dependent fashion, whereas nalmefene did not, in both n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Other than one human study reporting an increase in serum prolactin following intramuscular administration of naloxone 210 mg (Kumor et al, 1988), extensive studies in non-human primates and humans have not found an effect of this mu-opioid receptor antagonist on serum prolactin (Volavka et al, 1980;Morley et al, 1980;Naber et al, 1981;Cohen et al, 1983Cohen et al, , 1985van Bergeijk et al, 1986;VanVugt et al, 1989b). Data for naltrexone and nalmefene, the two antagonists with greater affinity at mu-and kappa-opioid receptors than naloxone, are, however, mixed.…”
Section: Prolactin and Mu-and Kappa-opioidergic Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other than one human study reporting an increase in serum prolactin following intramuscular administration of naloxone 210 mg (Kumor et al, 1988), extensive studies in non-human primates and humans have not found an effect of this mu-opioid receptor antagonist on serum prolactin (Volavka et al, 1980;Morley et al, 1980;Naber et al, 1981;Cohen et al, 1983Cohen et al, , 1985van Bergeijk et al, 1986;VanVugt et al, 1989b). Data for naltrexone and nalmefene, the two antagonists with greater affinity at mu-and kappa-opioid receptors than naloxone, are, however, mixed.…”
Section: Prolactin and Mu-and Kappa-opioidergic Drugsmentioning
confidence: 99%
“…One nonhuman primate study found that nalmefene suppressed basal prolactin, whereas its quaternary ammonium form, which does not penetrate the blood-brain barrier, had no effect on prolactin (Simpkins et al, 1991). Another study found that nalmefene had no effect on serum prolactin in male rhesus monkeys (Mello et al, 2000), while another group found that nalmefene stimulated prolactin release in normal female rhesus monkeys but not in ovariectomized monkeys (VanVugt et al, 1989b). Naltrexone 50 mg stimulated prolactin release in normal male volunteers, early follicular phase female volunteers, and, following daily dosing for 1 week, in luteal phase female volunteers (Volavka et al, 1979;Mendelson et al, 1986;Gindoff et al, 1988), although, when studied in males, naltrexone 100 mg had no effect on prolactin (Volavka et al, 1979).…”
Section: Prolactin and Mu-and Kappa-opioidergic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several explanations may account for this discrepancy: exogenous opiates may show pharmacological and not physiological effects; and apparently, some opiates have agonist activity, as well as antagonist activity (13). Furthermore, opiates differ in their relative affinity for different receptor subtypes (13,32), and the in vivo function of endogenous opioids may involve receptors that are relatively insensitive to naloxone (3,9,13,(33)(34)(35). Naloxone is a competitive inhibitor of opiate receptors; but in low doses, it has the highest affinity for -and ⑀-receptors, whereas relatively large doses are required to block the ␦-and -receptors (3,33).…”
Section: Discussionmentioning
confidence: 99%